1988
DOI: 10.1016/s0140-1971(88)80036-8
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐systemic analysis of anorexia nervosa

Abstract: Aspects of the eco‐systemic approach were used to provide a framework for the understanding of anorexia nervosa and were empirically tested by comparing 30 anorexics and their parents to 34 matched control subjects and their parents. The theoretical model employed was an adaptation of Conger's Ecological‐Systems approach which was based on the principles of Bronfenbrenner's theory of human development. The subjects were compared on selected variables arising from the individual, parent, family, and community s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…As a whole, the present results suggest that eating disorder patients appear to have decidedly negative interpersonal pro®les compared to relevant controls. Results support earlier ®ndings concerning anorexics and bulimics that have utilized the SASB (Friedman et al, 1997;Humphrey, 1988;Sheppy et al, 1988;Strauss & Ryan, 1987;Swift et al, 1986;Wonderlich et al, 1996), as well as ®ndings concerning EDNOS patients that have been based on the use of other measures (Mendelson et al, 2002). In particular, the pro®les of self-image among eating disorder patients appear to be distinguished by low levels of self-af®rmation and high levels of self-blame and self-hate.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As a whole, the present results suggest that eating disorder patients appear to have decidedly negative interpersonal pro®les compared to relevant controls. Results support earlier ®ndings concerning anorexics and bulimics that have utilized the SASB (Friedman et al, 1997;Humphrey, 1988;Sheppy et al, 1988;Strauss & Ryan, 1987;Swift et al, 1986;Wonderlich et al, 1996), as well as ®ndings concerning EDNOS patients that have been based on the use of other measures (Mendelson et al, 2002). In particular, the pro®les of self-image among eating disorder patients appear to be distinguished by low levels of self-af®rmation and high levels of self-blame and self-hate.…”
Section: Discussionsupporting
confidence: 84%
“…Swift, Bushnell, Hanson, and Logeman (1986) examined 30 hospitalized adolescent anorexics, and found them to have considerably more negative self-image than normal controls. Sheppy, Friesen, and Hakstian (1988) studied 30 anorexics between 15 and 23 years of age, and found them to have signi®cantly more negative forms of self-image compared to 34 matched controls. Friedman, Wil¯ey, Robinson Welch, and Kunce (1997) compared 37 adult binge eaters and 37 adult bulimics involved in in-patient treatment on all three SASB surfaces, and found that bulimics had greater levels of self-directed hostility compared to normal controls.…”
mentioning
confidence: 99%
“…1,2 Interpersonal factors are increasingly in focus in research on eating disorders (ED), where self-image negativity is a consistent finding, as are problematic relationships and family interaction patterns. [3][4][5][6] In this study, self-image was used to predict outcome in anorexia nervosa (AN) and bulimia nervosa (BN), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…19 In another study, an AN sample rated their mothers as expressing less affiliation and more control than normal controls, using a SASB measure of dyadic behavior. 20 Other forms of control such as perfectionism and obsessionality have been suggested as risk factors in AN, 21 and longitudinal findings suggest that different prospective risk factors relate to AN and BN, respectively. 22 In the latter study, young adulthood onset of AN was predicted by self-reported perfectionism during the teen years, whereas for BN, the predictor was negative or depressive affect.…”
Section: Introductionmentioning
confidence: 99%